Comprehensive literature review on delay tolerant network (DTN) framework for improving the efficiency of internet connection in rural regions of Malaysia - Perumal, Sundresan; Raman, Valliappan; Samy, Ganthan Narayana; Shanmugam, Bharanidharan; Kisenasamy, Karthiggaibalan; Ponnan, Suresh (International journal of system assurance engineering and management, 2022)
This paper brief in detail the technology reviews of current available technologies and literature reviews that starts with the history of the Internet and the understanding of the working of the Internet through a conceptual model of TCP/IP and OSI models, the numerous technologies developed to cater for different connectivity environments and recent popular topics in the field of communication technologies. Detailed review is done on the subject of Delay-Tolerant Networking (DTN), the chosen technology from which the intended framework can be proposed for improving the efficiency of internet connections. From these literatures, comparisons are made to find the best possible combinations of technologies to design a minimum viable product, followed by a generic DTN framework.